Crisis Construction and Organizational Learning: Capability Building in Catching-up at Hyundai Motor - Kim, Linsu (Organization Science, 1998)
Effective organizational learning requires high absorptive capacity, which has two major elements: prior knowledge base and intensity of effort. Hyundai Motor Company, the most dynamic automobile producer in developing countries, pursued a strategy of independence in developing absorptive capacity. In its process of advancing from one phase to the next through the preparation for and acquisition, assimilation, and improvement of foreign technologies, Hyundai acquired migratory knowledge to expand its prior knowledge base and proactively constructed crises as a strategic means of intensifying its learning effort. Unlike externally evoked crises, proactively constructed internal crises present a clear performance gap, shift learning orientation from imitation to innovation, and increase the intensity of effort in organizational learning. Such crisis construction is an evocative and galvanizing device in the personal repertoires of proactive top managers. A similar process of opportunistic learning is also evident in other industries in Korea.